Law As a Species of Language Acquisition - Jim Chen (Washington University Law Quarterly, 1995)
Without fanfare, Plain Meaning and Hard Cases relegated its discussion of phonetics, phonology, and morphology to a single footnote. One must strain to imagine how the mechanics of sound production or the sound system of the English language might affect the law. Linguistics at too high a level of abstraction likewise seems unhelpful. American law rarely considers the nuances of foreign languages,' and a fortiori the entire field of comparative linguistics, especially as applied in the ongoing search for linguistic universals, seemingly lies outside the useful domain of law and linguistics. This assumption is demonstrably wrong. To the extent that we legal writers might believe otherwise, we have only ourselves to blame. We have been misunderstanding the relation between law and linguistics all along.
Keywords: Linguistics